Enriching computing identity frameworks: integrating current constructs and unveiling new dimensions for today’s tech-savvy world—a systematic review - Santhosh, Malavika E.; Siby, Nitha; Sellami, Abdellatif; Bhadra, Jolly; Ahmad, Zubair (Frontiers in Education, 2024)
This systematic review seeks to improve the existing framework for developing students' Computing Identity (CI) by integrating contemporary elements and identifying new dimensions. A meticulous selection of 31 articles followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, ensuring a comprehensive and systematic approach. The findings highlight factors that influence students' CI and also the constructs defining the frameworks for developing students' CI. The identified existing constructs are competence/performance, interest, sense of belonging, and recognition in computing, with competence/performance being the most explored and recognition the least. The review proposes a new framework for developing students' CI that includes the "social context" as it interweaves with existing constructs to shape the multifaceted process of CI formation. The findings underscore a research gap concerning the inclusion of diverse perspectives, which is essential for a richer understanding of CI. Additionally, the study emphasizes the potential to incorporate new elements to enhance the existing frameworks for developing students' CI, along with its validation in diverse contexts.